Optimization of irrigation with treated wastewater on flower cultivations - Papadopoulos I.; Chimonidou D.; Savvides S.; Polycarpou P. (Non-conventional water use: WASAMED project, 2005)
This paper deals with the Optimization of irrigation with treated wastewater for the cut flowers: a) Gerbera jasmesonii and b) for hydroponic culture of Limonium perezii and Antirrhinum. Gerbera jasmesonii was irrigated with secondary treated wastewater, borehole water and fresh water with or without additional fertilization. Results showed that freshwater produced significantly more flowers per plant than the other water qualities and fertilization had a significant effect on flower production for freshwater irrigated plants but no significant effect on wastewater irrigated plants. Results on Limonium perezii and Antirrhinum in hydroponics, showed that both plants irrigated with secondary treated wastewater and treated wastewater from the epuvalisation system were less vigorous and produced significantly less flowers or lower quality than flowers produced from plants irrigated with freshwater with the addition of fertilizer. High salt concentration in wastewater can be a limiting factor for the production of sensitive plants such as Gerbera jasmesonii.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)